The Intersecting Timelines of Past and Present: From Personal to Collective Trauma in the Novelist Sinan Antoon’s “Jasim’s File” - Al Janabi , Hazem Kamel Abd; Az-Zubaidy, Thamir R. S. (Journal of Ecohumanism, 2024)
This paper investigates the disintegration of Iraq following the 2003 American invasion. It examines the impact of its aftermath in destroying sites of Iraqi knowledge and memory and shaping the traumatic experiences of Iraqi people as presented in Sinan Antoon’s story, “Jasim’s File” (2018). Accordingly, the story illustrates the impact of the American invasion in the dissemination of a fabricated or alternative reality. It demonstrates how different traumatic agents have asserted dominance and conveys the role of the American occupation of Iraq in turning personal traumas into collective ones. Thus, the paper highlights the intersection between trauma theory and postcolonial literary studies. Some of the premises of leading figures in trauma studies – Cathy Caruth, Dominick LaCapra, Marianne Hirsch, Dori Laub, and Roger Luckhurst – were inspected, to argue that Iraqi post-invasion fiction enriches the study of postcolonial trauma theory, especially when applied in an under-researched context such as Iraq. While exploring the traumatic experiences of two characters, Jasim and Zayn, the story casts light on the influence of wars, genocide, displacement, and invasion on the Iraqi people’s psyche. Further, it presents a context in which celebrating the therapeutic value of testimony increases rather than reduces the impact of trauma.